Drift and deposition of pesticide applied by UAV on pineapple plants under different meteorological conditions - Wang, Juan; Lan, Yubin; Zhang, Huihui; Zhang, Yali; Wen, Sheng; Yao, Weixiang; Deng, Jiajian (International Journal of Agricultural and Biological Engineering, 2018)
Spray drift has always been a focus research area in the field of unmanned aerial vehicle (UAV) application. Under the fixed premises of UAV operating parameters, such as height, speed and spraying liquid, the droplet drift is mainly affected by meteorological conditions. In this research, the spray drift and deposition tests were conducted using a QuanFeng120 UAV in a pineapple field under various different meteorological conditions. The experimental results showed that with the changes of UAV operating height and wind speed, the start position of the in-swath deposition area changed 4 m in the extreme situation. The percentage of the total spray drift was from 15.42% to 55.76%. The position of cumulative spray drift that accounted for 90% of the total spray drift was from 3.70 m to 46.50 m relative to the flight line. According to the downwind spray drift curve, the nonlinear equations of the same type under the four operating conditions of the UAV were fitted. The spray drift and the deposition of UAV application were significantly affected by different meteorological conditions and UAV operating heights. The results could provide a theoretical basis for UAV spraying in pineapple plants and support for spray drift control and prediction. Keywords: UAV, spray drift, deposition, meteorological condition, pineapple DOI: 10.25165/j.ijabe.20181106.4038 Citation: Wang J, Lan Y B, Zhang H H, Zhang Y L, Wen S, Yao W X, et al. Drift and deposition of pesticide applied by UAV on pineapple plants under different meteorological conditions. Int J Agric & Biol Eng, 2018; 11(6): 5–12.